2022
DOI: 10.14309/ajg.0000000000002123
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Celiac Disease in Patients With Liver Diseases: A Systematic Review and Meta-Analyses

Abstract: INTRODUCTION: A subset of patients with celiac disease (CeD) has liver involvement in the form of hypertransaminasemia, liver cirrhosis, and autoimmune hepatitis. We conducted a systematic review with meta-analyses to determine the pooled prevalence of CeD in patients with cryptogenic cirrhosis, all-cause cirrhosis, cryptogenic hypertransaminasemia, and all-cause hypertransaminasemia. METHODS:We searched PubMed and EMBASE up to January 2022. Cross-sectional, case-control, and prospective cohort studies perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 61 publications
1
8
0
2
Order By: Relevance
“…Yoosuf et al (1) confirmed that CD is associated with cryptogenic cirrhosis finding a pooled prevalence of CD of 4.6% in patients with cryptogenic cirrhosis. CD was found in 0.8% of cases of cirrhosis from any cause, which mirrors the population prevalence of CD (1).…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…Yoosuf et al (1) confirmed that CD is associated with cryptogenic cirrhosis finding a pooled prevalence of CD of 4.6% in patients with cryptogenic cirrhosis. CD was found in 0.8% of cases of cirrhosis from any cause, which mirrors the population prevalence of CD (1).…”
mentioning
confidence: 95%
“…CD was also identified in unexplained hypertransaminasemia in 5.7% of patients (1). Numerous diseases were ruled out before labeling the patients as unexplained (cryptogenic) hypertransaminasemia.…”
mentioning
confidence: 99%
See 3 more Smart Citations